2014
DOI: 10.1007/s40030-014-0100-0
|View full text |Cite
|
Sign up to set email alerts
|

Review on Current Research Status on Bottom Ash: An Indian Prospective

Abstract: India focuses on attention towards ''greener and cleaner'' environment surrounding us. For that, the engineers and scientists have joined hands together to accept the challenges for recycling wastes from industries. The generation of Bottom Ash (BA) from thermal power plants which are being increased day by day and facing disposal and environmental problems. In spite of that, it is being used as landfills which has no commercial value, but now needs to think on its utilization as useable supplementary material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 69 publications
1
16
0
Order By: Relevance
“…The chemical analysis based on SEM-EDS results indicates that the main chemical compounds including silicates (SiO 2 ), aluminates (Al 2 O 3 ), and iron oxide (Fe 2 O 3 ) with other compounds in trace amounts. This result is consistent with the previous studies [21] reporting that silicates (SiO 2 ) was found the most abundant, aluminates (Al 2 O 3 ) was found the second most abundant constituent, followed by iron oxide (Fe 2 O 3 ).…”
Section: Physicochemical and Leaching Properties Of Bottom Ash (Ba)supporting
confidence: 93%
See 1 more Smart Citation
“…The chemical analysis based on SEM-EDS results indicates that the main chemical compounds including silicates (SiO 2 ), aluminates (Al 2 O 3 ), and iron oxide (Fe 2 O 3 ) with other compounds in trace amounts. This result is consistent with the previous studies [21] reporting that silicates (SiO 2 ) was found the most abundant, aluminates (Al 2 O 3 ) was found the second most abundant constituent, followed by iron oxide (Fe 2 O 3 ).…”
Section: Physicochemical and Leaching Properties Of Bottom Ash (Ba)supporting
confidence: 93%
“…As is evident by SEM images and energy-dispersive X-ray spectroscopy (EDS) displayed in Figure 2, BA used in this study consisted of mesoporous and spherical particles. This observation is mainly due to both melting and expelling of ash from BA particles through high temperature and pressure processes of pulverized coal-fired combustion [21]. In a pulverized coal-fired combustion, the furnace operating temperatures are typically over 1400 • C, where most mineral matters within the coal could be oxidized, decomposed, fused, disintegrated, or agglomerated [22].…”
Section: Physicochemical and Leaching Properties Of Bottom Ash (Ba)mentioning
confidence: 99%
“…In a thermal power plant, there are two types of ashes; bottom ash and fly ash [71]. Bottom ash is generally larger in size and hence there is possibility of lesser concentrations of heavy metals on their surface [72] while the fly ash is finer in size, so comparatively there will be higher concentrations of heavy metals on their surface [72]. The composition of heavy metals along with other elements present in fly ash aqueous solution is given below in Table 1.…”
Section: Inductively Coupled Plasma Analysis Of Fly Ash Digested Samplementioning
confidence: 99%
“…The increased demand for energy requirement of the industry results in increased production of CCR during the coal combustion process such as pulverized coal combustion (PCC) and fluidized bed combustion (FBC). By the year 2020, it is being expected that about 190 million tons of CCR will be generated in India per annum (CEA, 2011; Mandal and Sinha, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The physicochemical characteristics of coal combustion residues are controlled by the use of types of coal, boiler and its operating temperatures. Due to the high temperature of the PCC boiler, melting of ash occurred, resulting in the formation of bulk agglomerated gas entrapped bottom ash (Kim, 2002; Kutchko and Kim, 2006; Senior et al, 2000); whereas, bottom ash produced in the FBC boiler consists of free non-agglomerated particles due to lower temperature generation (<1000°C) (Mandal and Sinha, 2014, 2017a, 2017b, 2017c). The bottom ash produced during the FBC process is attracting more attention due to the novelty of coal combustion technology.…”
Section: Introductionmentioning
confidence: 99%